International medical graduates in the USA: a qualitative study on perceptions of physician migration. Issue 2 (12th September 2011) - Chen, P G; Nunez-Smith, M; Berg, D; Gozu, A; Rulisa, S; Curry, L A
Abstract : Objectives: Physician migration from low-income to high-income nations is a global concern. Despite the centrality of understanding the perspectives of international medical graduates (IMGs) who have experienced migration to understanding the causes and consequences of this phenomenon, empirical literature is limited. The authors sought to characterise the experiences of IMGs from limited resource nations currently practicing primary care in the USA, with a focus on their perspectives on physician migration. Design: The authors conducted a qualitative study utilising in-depth, in-person interviews and a standardised interview guide. The sample comprised a diverse, purposeful sample of IMGs (n=25) from limited resource nations (defined as having ≤2 physicians per 1000 population). Results: Analyses revealed four recurrent and unifying themes reflecting the perspectives of IMGs in the USA on physician migration: (1) decisions to migrate were pragmatic decisions made in the context of individual circumstance; (2) the act of migration ultimately affected participants' ability to return home in multiple, unpredictable ways; (3) the ongoing process of acclimation was coupled with inherent conflicts surrounding the decision to remain in the USA; and (4) the effects of policies in both the home country and in the USA occurred at multiple levels. Conclusion: The perspectives of IMGs who have migrated to the USA are an important addition to the ongoing discussion surrounding the global health workforce. Our findings highlight the effects of workforce policies which are often developed and discussed in abstraction, but have real, measurable impacts on the lives of individuals. Future efforts to address physician migration will need to acknowledge the immediate needs of the health workforce as well as the long-term needs of individuals within health systems.